On humanitarian virality: Kony 2012, or, the rise and fall of a pictorial artifact in the digital age. (August 2019) - Kurasawa, Fuyuki
This article adopts a socio-visual constructivist approach to explain how the Kony 2012 video became a site of intense symbolic struggle regarding how to represent humanity in the digital age and, in the process, one of the most viral and intensely contested cultural artifacts of the last few years. The first section demonstrates that the video employs the visual conventions of personification and rescue, which form part of an iconographic repertoire coding certain events as humanitarian crises recognizable as such by Euro-American audiences. Conversely, the author examines how these tropes drew upon a neocolonial framing of humanitarianism, one that Ugandan and Western critics questioned and against which they offered an alternative vision of the post-civil war realities of northern Uganda. However, to avoid pictorial reification, the article's second section retraces the institutional and actor-based networks through which still and moving images from Kony 2012 and its associated campaign circulated. The concept of pictorial exponentiality is introduced to explain how these images multiplied in digital public spaces through the accelerating digital cycles. This section also examines the concept of digital feedback loops to make sense of the non-linear and institutionally 'flattened' social relations binding pictorial actors debating the video's representational content and responding to each other via social media- and web-based exchanges. Kony 2012 was a key marker of an era during which the visual politics and ethics of portrayal of the human unfold digitally, through social media and online video platforms as much as conventional institutions of image production and dissemination. By treating the video as a cultural artifact whose viral rise and fall are attributable to the pictorial conventions upon which it drew and the structure of the networks through which it circulated, the article reveals how understandings of humanity are visually constituted, contested, and undone in the digital age.